ISOTHERMAL OXIDATION BEHAVIOUR OF 69,5Fe-14Ni-9Al-7,5Cr ALLOY AT 800, 900, dan 1000C - C Nababan (NIM : 12513018), Deddy
Population growth, globalÃ‚Â’s economy and technological developments affect the increase in world-wide electricity demand. The electricity demand is predicted to increase by 25% from 2014 to 2040. The production of electricity depends on the efficiency of the generator machine used. An increase in operating temperature will increase the efficiency of energy acquisition. This is the reason for various studies conducted to find material that can survive in these conditions. The advanced ferritic steel with alloy elements Ni, Al, and Cr are alternative materials used in some parts of power plant construction because it has a low thermal expansion coefficient and a relatively have price cheaper compared to nickel-based super alloys. In addition, the ferritic steel has an advantage because it can be strengthened with coherent precipitate B2. And also, the Al and Cr content can increase oxidation resistance at elevated temperatures. A series of experiments have been conducted to study the resistance of isothermal oxidation in 69.5Fe-14Ni-9Al-7,5Cr (% wt) alloys with some temperature variations of 800, 900, and 1000oC and each temperature is tested for 1, 10, 50, and 150 hours. Experimental is done using horizontal tube furnace with free air environment condition. Weighing is done to the sample before and after the test to have the change of weight that happened. The data of weight change on the surface area of each sample is then processed to determine the behavior of its resistance and also its oxidation rate. The samples is characterized using some equipment such as OM (optical microscope), XRD (X-Ray Diffraction), and SEM-EDS (Scanning Electron Microscope-Energy Dispersive X-Ray Spectroscopy) then. High temperatures condition also involves changes in the precipitate micro structure. Based on the analysis conducted on the test results, it is known that the higher oxidation temperature, the faster oxidation rate. As for the duration of oxidation, the longer the testing time, the weight change per unit sample area is smaller indicated by a sloping graph. The oxide products found in this study were Fe2O3, Fe3O4, -Al2O3, NiO, Cr2O3 and NiCr2O4. The rate of oxidation of this alloy at each temperature follows a logarithmic equation indicating that the oxide layer formed is very thin and can protect the metal surface well. The oxidation rate constants at temperatures of 800, 900 and 1000oC are 5.15E-05, 5,57E-05 and 6,74E-05 gr.cm-2, respectively. If viewed based on test conditions done on this study, this alloy is better operated at a maximum temperature of 800oC because the spalling of the oxide layer is found to be very small.